Activity fields and the dynamics of crime - Wikström, Per-Olof H. (Journal of quantitative criminology, 2010)
Our current understanding of the role of the social environment in crime causation is at best rudimentary. Guided by the theoretical framework of Situational Action Theory, and using data from the ESRC financed Peterborough Adolescent and Young Adult Development Study (PADS+), this paper aims to propose how we can better theorise and study the role of the social environment, particularly the person and place interaction, in crime causation. We will introduce, and illustrate the usefulness of, a space–time budget methodology as a means of capturing people’s exposure to settings and describing their activity fields. We will suggest and demonstrate that, combined with a small area community survey and psychometric measures of individual characteristics, a space–time budget is a powerful tool for advancing our knowledge about the role of the social environment, and its interaction with people’s crime propensity, in crime causation. Our unique data allows us to study the convergence in time and space of crime propensity, criminogenic exposure and crime events. As far as we are aware, such an analysis has never before been carried out. The findings show that there are (a) clear associations between young people’s activity fields and their exposure to criminogenic settings, (b) clear associations between their exposure to criminogenic settings and their crime involvement, and, crucially, (c) that the influence of criminogenic exposure depends on a person’s crime propensity. Having a crime-averse morality and strong ability to exercise self-control appears to make young people practically situationally immune to the influences of criminogenic settings, while having a crime-prone morality and poor ability to exercise self-control appears to make young people situationally vulnerable to the influences of criminogenic settings.